2018
DOI: 10.1186/s40795-018-0228-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between feeding practices and growth and neurodevelopmental outcomes at 36 months among children living in low- and low-middle income countries who participated in the BRAIN-HIT trial

Abstract: Background: Feeding practices over the first several years of a child's life can critically influence development. The purpose of this study was to examine associations between feeding practices and growth and neurodevelopmental outcomes at 36 months of age among children from low-and low-middle-income countries (LMIC). Methods: We conducted a secondary analysis using data collected from children in India, Pakistan, and Zambia who were enrolled in a randomized controlled trial of a home-based early development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The modifications made to assess the feeding practices among the children aged ≥ 24 months, as well as combining two food groups, were consistent with the previously published study of Do et al (2018) [24]. The details of the indicators and the modifications are available in Supplementary Table S1.…”
Section: Feeding Indicatorsmentioning
confidence: 55%
See 1 more Smart Citation
“…The modifications made to assess the feeding practices among the children aged ≥ 24 months, as well as combining two food groups, were consistent with the previously published study of Do et al (2018) [24]. The details of the indicators and the modifications are available in Supplementary Table S1.…”
Section: Feeding Indicatorsmentioning
confidence: 55%
“…MDD: this indicator was considered achieved when receiving foods from at least four out of the six food groups [24]; 2.…”
Section: Feeding Indicatorsmentioning
confidence: 99%
“…Vitamin D deficiency may also affect body composition. A cross-sectional analysis including 271 healthy community-dwelling elderly individuals has reported that lower vitamin D levels are associated with increased fat mass and visceral adipose tissue [ 16 ]. Other studies have confirmed the relationship between lower vitamin D levels and total and android body fat, waist circumference (WC), and waist-to-hip ratio [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%